The justification of God? The story of God's work according to Jürgen Moltmann : Part 1 - Conradie, Ernst M. (Scriptura, 2008)
This essay reconstructs the way in which Jürgen Moltmann tells the story of God's work. This is done on the basis of a review essay by Douglas Farrow who identifies a neo-Platonic structure in Moltmann's systematic contributions to theology. The argument of this essay is that Moltmann fails to distinguish adequately between creation and fall. This has significant implications for his understanding of salvation, church and eschatological consummation. In this way theology becomes preoccupied with the doctrine of providence and thus with the theodicy problem.